Analisis Pengaruh Perhatian Investor pada Masa Penawaran Umum Perdana (IPO) terhadap Volatilitas Harga Saham Pasca IPO Ahmad Dwi Murdani* dan Buddi Wibowo - Murdani, Ahmad Dwi; Wibowo, Buddi (Masyarakat Ekonomi Syariah Bogor, 2025)
This study examines the effect of investor attention during the Initial Public Offering (IPO) period on the stock prices volatility after the shares are listed and traded on the Indonesia Stock Exchange (IDX). This study uses data on the shares of issuers who have conducted an IPO on the IDX after the implementation of the electronic Initial Public Offering (e-IPO) mechanism, with the aim of being able to capture the phenomenon of retail investor behavior. The method used in this study is the regression method. This study shows that the level of investor attention during the IPO period influences the stock price volatility on short-term dan medium-term investment horizon.